Implementing interprofessional video consultations with general practitioners and psychiatrists in correctional facilities in Germany: results from a mixed-methods study - Miriam Giovanna Colombo; Stefanie Joos; Roland Koch (BMC, 2023)
Abstract Background Adequate health care in correctional facilities is often limited by staff shortage, which entails time-consuming consultations with physicians outside of these facilities. Video consultations (VC) have been implemented in many different health care settings and may also be useful in correctional facilities. As part of a pilot project, synchronous VC were implemented in five correctional facilities in Germany in June 2018. The aim of this study was to describe the implementation process from the providers' perspective and to identify factors promoting or inhibiting the implementation process of VC with a focus on interprofessional collaboration between nursing staff and telemedicine physicians. Methods As part of the mixed-methods evaluation of the pilot project, site visits to the five correctional facilities were carried out. Nursing staff from the five correctional facilities (n=49) and telemedicine physicians (n=10) were asked to participate in interviews and a questionnaire survey. Interviews were analyzed using qualitative content analysis and questionnaires were evaluated using descriptive statistical methods. The results from both data sources were integrated and discussed in the framework of Normalization Process Theory. Results Interviews were conducted with 24.5% (n=12) of nursing staff and 20.0% (n=2) of telemedicine physicians, while questionnaires were returned by 22.5% (n=11) of nursing staff and 33.3% (n=3) of telemedicine physicians. VC with general practitioners and psychiatrists were perceived as an additional support during times when physicians were absent from the correctional facilities. Allocating telemedicine physicians to specific correctional facilities might further improve interprofessional collaboration with nursing staff during VC. Inhibiting factors comprised the lack of integrating nursing staff into the implementation process, increased workload, insufficient training and the implementation of VC at an inconvenient time. Conclusions To summarize, VC are a promising supplement to face-to-face health care in correctional facilities despite several limitations. These might be compensated by improving interprofessional cooperation and by integrating telemedicine physicians into local health care teams.